Palliative long-term abdominal drains for the management of refractory ascites due to cirrhosis: a consensus document. Issue Volume 13:Issue e1(2022) (10th June 2022) - Macken, Lucia; Corrigan, Margaret; Prentice, Wendy; Finlay, Fiona; McDonagh, Joanne; Rajoriya, Neil; Salmon, Claire; Donnelly, Mhairi; Evans, Catherine; Ganai, Bhaskar; Bedlington, Joan; Steer, Shani; et al.
Abstract : Palliative care remains suboptimal in advanced cirrhosis, in part relating to a lack of evidence-based interventions. Ascites remains the most common cirrhosis complication resulting in hospitalisation. Many patients with refractory ascites are not candidates for liver transplantation or transjugular intrahepatic portosystemic shunt, and therefore, require recurrent palliative large volume paracentesis in hospital. We review the available evidence on use of palliative long-term abdominal drains in cirrhosis. Pending results of a national trial (REDUCe 2) and consistent with recently published national and American guidance, long-term abdominal drains cannot be regarded as standard of care in advanced cirrhosis. They should instead be considered only on a case-by-case basis, pending definitive evidence. This manuscript provides consensus to help standardise use of long-term abdominal drains in cirrhosis including patient selection and community management. Our ultimate aim remains to improve palliative care for this under researched and vulnerable cohort.